(untitled) (Journal on studies and research of academic knowledge, 2022)
The proposal focuses on the determination of the best productive practices applicable to agro-livestock and environmental production, for the northern part of the Eastern Region of Paraguay, with the aim of reducing factors that could affect soil erosion and the loss of productive vocation. The Analytic Hierarchy Process, developed by Thomas L. Saaty, was applied, studied and applied by various authors. Alternatives were evaluated to support decision-making regarding the best conservationist productive practices, classifying them into three alternatives: Livestock, Agriculture and Silvopastoral, with criteria such as Forest Cover; Erosion, with subcriteria of slope and rain; Land use aptitude, with skill-based sub-criteria, set out in Classes three and four. The results reveal that in 51.82%, of the cases, the Agricultural activity presents better production conditions, due to the soil conditions that are suitable for this practice; in 27.85% of the cases, the soils are considered to be optimal for silvopastoral practice, while in 20.32% of the cases, conditions suitable for livestock production are presented, given the environmental conditions